George Friedman, The Next Decade: Empire and Republic in a Changing World - Ms. Hajira Asaf Khan (CISS Insight Journal, 2015)
Friedman begins the book with a chapter entitled “The Unintended Empire”. This is an allusion to the pre-eminent place of the United States in the current world power structure and the measure of influence it can exert over the global economy as well as being the largest and most technologically advanced country, with great military strength. However, he points out that being founded on the basis of an antiimperialist struggle, the United States of America does not seem to be comfortable with that position in the world. There is tension between the anti-imperialist idealism rooted in America’s psychological make up and immense power it has at its disposal to shape the world events. This duality has affected America’s identity and the author suggests that American leaders should work to address this crisis of identity. In other words, the US seems to like having power without having to face the responsibilities that comes with it.